Biodiversity and distribution of zoobenthos in the ecological water replenishment area of the Yellow River estuary coastal wetland revealed by eDNA metabarcoding - Xie, Gang; Lan, Jie; Liang, Jinhui; Wang, Qidong; Cao, Xiaoqiang; Wang, Yanlong; Ren, Chongyang; Liu, Huaqing; Zhang, Jian (PLOS ONE, 2024)
The coastal wetland of the Yellow River Estuary, one of China’s largest wetlands, is essential for biodiversity conservation and ecosystem services. Ecological water replenishment, a typical wetland restoration measure in the Yellow River Delta, has significantly impacted the habitat of zoobenthos, which are critical indicators of ecosystem health and water quality. However, the community characteristics of zoobenthos in this coastal wetland are poorly understood. This study utilized eDNA metabarcoding to assess the diversity and community structure of zoobenthos in the ecological water replenishment area of Yellow River Estuary Coastal Wetland. Zoobenthos from 174 families were identified, with 307 species recognized at the generic level, significantly more than those identified through traditional morpho-taxonomic approaches. Salinity emerged as a crucial factor in shaping these ecosystems. Contrary to expectations, in this study, brackish water exhibited the lowest species richness compared to freshwater and seawater, which may be attributed to local environmental stressors and fluctuating salinity conditions in the Yellow River Estuary. Environmental factors such as salinity, organic matter, and nutrient elements significantly influence the composition and distribution of zoobenthos. Specifically, cations, particularly Mg2⁺ and Ca2⁺, have a more substantial impact on zoobenthos than anions. Our results provide crucial information on zoobenthic biodiversity within ecological water replenishment areas, offering insights into the ecological dynamics and environmental factors shaping zoobenthos communities under ecological management.